Zakat, Islamic Corporate Social Responsibility Dan Kinerja Keuangan Bank Umum Syariah Indonesia - Yolanda Septian; Any Eliza; Muhammad Yusuf Bahtiar (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2022)
This research aims to examine the effect of zakat and Islamic Corporate Social Responsibility (ICSR) on the financial performance of Sharia Commercial Banks in Indonesia for the 2016-2019 period. This research uses quantitative method. The data uses is secondary data in the from of the annual report of Sharia Commercial Banks registered with the OJK for the 2016-2019 period. The data is collected by using documentation method and literature study method. The data analysis method used is descriptive statistical analysis and regression analysis. The population used is Sharia Commercial Banks in Indonesia registered with the OJK for the 2016-2019 totaling 14 Sharia Commercial Banks, with samples that meet criteria, namely 12 Sharia Commercial Banks, and the sampling technique in this research uses purposive sampling technique. The results obtained in this research are that zakat has a significant effect on the financial performance of Sharia Commercial Banks. And Islamic Corporate Social Responsibility does not effect the financial performance of Sharia Commercial Banks because the greater the ICSR disclosure value in Sharia Commercial Banks does not make the financial performance of Sharia Commercial Banks god or bad and vice versa.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh zakat dan Islamic Corporate Social Responsibility (ICSR) terhadap kinerja keuangan Bank Umum Syariah di Indonesia periode 2016-2019. Penelitian ini menggunakan metode kuantitatif. Data yang digunakan adalah data sekunder berupa laporan tahunan Bank Umum Syariah yang terdaftar di OJK periode 2016-2019. Metode pengumpulan data yang digunakan adalah metode dokumentasi dan metode studi pustaka. Metode analisis data yang digunakan adalah analisis statistik deskriptif dan analisis regresi logistik. Populasi yang digunakan yaitu Bank Umum Syariah di Indonesia yang terdaftar di OJK periode 2016-2019 berjumlah 14 Bank Umum Syariah, dengan sampel yang memenuhi kriteria yaitu 12 Bank Umum Syariah, dan teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling. Hasil yang diperoleh dalam penelitian ini adalah zakat berpengaruh signifikan terhadap kinerja keuangan Bank Umum Syariah. Dan Islamic Corporate Social Responsibility tidak berpengaruh terhadap kinerja keuangan Bank Umum Syariah dikarenakan semakin besar nilai pengungkapan ICSR dalam suatu Bank Umum Syariah tidak membuat kinerja keuangan Bank Umum Syariah menjadi baik ataupun buruk dan begitu juga sebaliknya.